Family Structure, Institutions, and Growth: The Origins and Implications of Western Corporations - Greif, Avner (American Economic Review, 2006)
siders the importance of the family as an institution. Little attention, however, has been given to the impact of the family structure and its dynamics on institutions. This limits our ability to understand distinct institutional developments-and hence growth-in the past and present. This paper supports this argument by highlighting the importance of the European family structure in one of the most fundamental institutional changes in history and reflects on its growth-related implications. What constituted this change was the emergence of the economic and political corporations in late medieval Europe. Corporations are defined as consistent with their historical meaning: intentionally created, voluntary, interest-based, and self-governed permanent associations. Guilds, fraternities, universities, communes, and city-states are some of the corporations that have historically dominated Europe; businesses and professional associations, business corporations, universities, consumer groups, counties, republics, and democracies are examples of corporations in modern societies. The provision of corporation-based institutions to mitigate problems of cooperation and conflict constituted a break from the ways in which institutions had been provided in the past. Historically, large kinship groups-such as clans, lineages, and tribes-often secured the